PEMBIAYAAN KUR BSI UNTUK PERKEMBANGAN UMKM DI DESA EMBONG IJUK KABUPATEN KEPAHIYANG - Dinda Murah Ati; Fia Nopitasari; Pepi Pepi; Fatimah Yunus; Adi Setiawan (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2021)
ABSTRACTThe People's Business Credit (KUR) is a Government Program in the context of empowering UMKM. This is a program that has been implemented by Bank BSI to assist in the development of UMKM through the KUR program. The aim is to see the KUR financing in Kepahiang Regency on the development of UMKM in Embong Ijuk Village. The benefits of the results of this study are expected to be useful information for UMKM actors in the Kepahiyang Muslim community to provide information on KUR funding from the Indonesian Sharia Bank (BSI) Kepahiyang unit. This type of research is qualitative in the form of descriptions, documentation and interviews. Informants recruited using this research technique consisted of many BSI workers involved in funding the KUR BSI Kepahiang unit. The results of this study indicate that capital growth,sales turnover and profits have increased significantly.Keywords: BSI, KUR, UMKMÂ